Physico-chemical Characterization of Tofu By-Product Silage Supplemented with Fine Rice Bran and Chestnut Tannin as Silage Additives - Sadarman, Sadarman; Harahap, Rakhmad Perkasa; Azmi, Amirul Faiz Mohd; Febrina, Dewi; Febriyanti, Rahmi; Gholib; Yunilas; Qomariyah, Novia; Nurfitriani, Rizki Amalia; Khairi, Fitrah (Faculty of Animal Science, Universitas Brawijaya, 2024)
This study seeks to evaluate the physico-chemical properties of tofu waste silage with the inclusion of refined rice bran and chestnut tannins as additives. This study employed an experimental method using a completely randomized design, comprising four treatments and five replications. The treatments included are T1: Fresh Tofu Waste (FTW as control), T2: FTW + 5% fine rice bran (DM basis), T3: FTW + 1% chestnut tannin (DM basis), and T4: FTW + 5% fine rice bran + 1% chestnut tannin (DM basis). The variables measured were temperature, humidity, pH, mold growth, aroma, texture, color, and dry matter loss. The data collected were analyzed using analysis of variance (ANOVA), and Duncan's multiple range test was applied at a 5% significance level to assess significant differences between treatments. The findings revealed that the inclusion of fine rice bran and chestnut tannin had a significant impact (P<0.05) on the temperature, humidity, pH, mold growth, aroma, texture, color, and dry matter loss of fresh tofu waste silage. In conclusion, the addition of 5% fine rice bran and 1% chestnut tannin resulted in tofu waste silage with superior physico-chemical quality, as evidenced by the lowest dry matter loss compared to the other treatments.